2006
DOI: 10.1080/02770900600567056
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia is a Potential Risk Factor for Asthma

Abstract: Hypercholesterolemia is a potential risk factor for asthma independent of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 21 publications
4
64
0
2
Order By: Relevance
“…It has been suggested that leptin might be involved in the pathogenesis of asthma in overweight children and that interferon-c might be a pathway in the process of leptin-induced inflammation [33,34]. A more recent study indicated a higher prevalence of asthma in children with high serum cholesterol [35]. The study was very small (n5188) and has not yet been reproduced.…”
Section: Discussionmentioning
confidence: 71%
“…It has been suggested that leptin might be involved in the pathogenesis of asthma in overweight children and that interferon-c might be a pathway in the process of leptin-induced inflammation [33,34]. A more recent study indicated a higher prevalence of asthma in children with high serum cholesterol [35]. The study was very small (n5188) and has not yet been reproduced.…”
Section: Discussionmentioning
confidence: 71%
“…Some epidemiologic studies suggest that waist circumference-defined abdominal adiposity, one of the characteristics of the metabolic syndrome, is more strongly associated with prevalent asthma than is BMI-defined obesity (7,8). This has led to some authors suggesting that the association of BMI-defined obesity with asthma may be mediated by the metabolic syndrome (9)(10)(11)(12). It is also not known whether the metabolic syndrome overall or its individual components are stronger predictors for incident asthma than BMI.…”
mentioning
confidence: 96%
“…Recently, asthma has been associated with insulin resistance, 22 dyslipidemia, 23,24 and metabolic syndrome, 25 measures of metabolic dysregulation that develop in some but not all obese children. 26,27 Moreover, genetic and epigenetic differences in molecules involved in metabolic dysregulation and its associated inflammation have been found in the context of obesityrelated asthma.…”
Section: Mechanisms Linking Obesity and Asthmamentioning
confidence: 99%